Personal wellbeing among adolescents and youth in India - Ratra, Dhriti; Singh, Kamlesh (Frontiers in Psychology, 2022)
The present study sought to explore the level of personal well-being and identify the determinants of happiness among Indian adolescents and youth. Data was collected from a sample of 495 participants (aged 11-23) residing in the National Capital Region of Delhi (Delhi-NCR), using the bilingual version (Hindi and English) of the Personal Well-Being Index (PWI). Their PWI score was 80.06, indicating high happiness levels in the non-western normative PWI range. Domains of personal relationships, community connectedness, and safety represented high overall well-being with the highest mean scores. Multivariate analysis showed that the least happy group on life as a whole domain were students aged 19-23 years as compared to the 11-14 and 15-18 years age group. Further, males had higher happiness levels on personal safety, while females had higher scores on life achievement. Qualitative analysis illustrated the socio-cultural basis of these well-being determinants as rooted in the hierarchical social structures and collectivistic cultural orientation.